Field to palette : the soil art dialogues - Toland, Alexandra, 1975-; Noller, Jay S.; Wessolek, Gerd, 1953- (Boca Raton : CRC Press, Taylor & Francis Group, 2018)
Respect for and conservation of soil, as a growing medium and as an artists' material.
OCLC-licensed vendor bibliographic record.
Keywords: Soil conservation; Soil management; Artists' materials; TECHNOLOGY & ENGINEERING / Agriculture / General; NATURE / Environmental Conservation & Protection; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General